The Impact of Stress and Major Depressive Disorder on Hippocampal and Medial Prefrontal Cortex Morphology - Belleau, Emily L. (Biol Psychiatry, 2018)
Volumetric reductions in the hippocampus and medial prefrontal cortex (mPFC) are among the most well documented neural abnormalities in major depressive disorder (MDD). Hippocampal and mPFC structural reductions have been specifically tied to MDD illness progression markers, including greater number of major depressive episodes (MDE), longer illness duration, and non-remission/treatment resistance. Chronic stress plays a critical role in the development of hippocampal and mPFC deficits, with some studies suggesting that these deficits occur irrespective of MDE occurrence. However, preclinical and human research also points to other stress-mediated neurotoxic processes, including enhanced inflammation and neurotransmitter disturbances, which may require the presence of a MDE and contribute to further brain structural decline as the illness advances. Specifically, hypothalamic-pituitary-adrenal axis dysfunction, enhanced inflammation and oxidative stress, and neurotransmitter abnormalities (e.g., serotonin, glutamate, gamma-Aminobutyric acid) likely interact to facilitate illness progression in MDD. Congruent with stress-sensitization models of MDD, with each consecutive MDE, it may take lower levels of stress to trigger these neurotoxic pathways leading to more pronounced brain volumetric reductions. Given that stress and MDD have overlapping and distinct influences on neurobiological pathways implicated in hippocampal and mPFC structural decline, further work is needed to clarify which precise mechanisms ultimately contribute to MDD development and maintenance.